Factors of Language Shift in Gayonese at Southeast Aceh Regency - Dina Sartika; Winda Setiasari; Anni Holila Pulungan (RETORIKA: Jurnal Ilmu Bahasa, 2023)
Language is an important marker of ethnic identity. It refers to language shift happens when a group of speakers utilizes a language from a broader society, such as a majority or national language, less frequently or stops speaking their mother tongue or a minority language.This study aims to find out the factors influence language shift of children in Jambur Damar village Southeast Aceh Regency. The Gayo dialect, the native tongue of Jambur Damar village in Southeast Aceh Regency. This study applied descriptive qualitative research method. The study subject were ten children of Jambur Damar village Southeast Aceh Regency. Furthermore, observation, interview and documentation were employed in collecting the data. After collecting the data, it was analyzed by the following stages, collecting, classifying, analyzing, and deciding. The findings showed that the two factors found that influence language shift from Gayonese to Indonesian namely internal factors and external factors. Internal factors are parents/family and intermarriage. Meanwhile, external factors are education/school and bilingualism. The most dominant one is intermarriage factors that influence language shift of children in Jambur Damar village Southeast Aceh Regency.